Manhaj Tarjih Dan Tajdid : Asas Pengembangan Pemikiran dalam Muhammadiyah - Setiawan, Bahar Agus (Universitas Muhammadiyah Jember, 2019)
This literature review aims at exploring both manhaj tarjih and tajdid in Muhammadiyah tradition as a basis for developing reasonings. Islamic study within Muhammadiyah tradition is not only intended for use in studying religious beliefs, but also as a process for understanding Islam more comprehensively, so that it can optimize the value of Islam as ?rahmatan lil alamin? not only at the conceptual level but also, more importantly, at the practical level in line with the philosophy of baldatun toyyibatun wa rabbun ghofur. The basis for developing thoughts in Muhammadiyah is predicated upon 16 main points, the rules of tarjih based on ijma', qiyas, maslahah mursalah and al-urf, while the tarjih method covers bayani, burhani and istislahi such as pertaining to reasoning for using bayani, burhani and irfani.